Public values and administrative reforms in French health care. Issue 3 (8th February 2016) - Simonet, Daniel
Abstract : Public value appears to be reborn out of the ashes of earlier failed new public management (NPM)‐driven policies in health care. It advocates greater consultation of the civic society and autonomy of public managers in decision‐making. In France, the 2009 Hospital, Patient, Health, and Territory law recentralized the health system and strengthened the central government to restore consistency in policy implementation and address earlier NPM shortcomings. The 2014 Health Project heralds a phase of policy hybridization that not only preserves earlier NPM tools but also seeks to reaffirm the role of the public and the medical profession in the governance of the health system. Copyright © 2016 John Wiley & Sons, Ltd.